# Find the difference of the arithmetic progression given by the formula an = -3n-3.

July 23, 2021 | education

| We need to find the difference of the arithmetic progression.

We know that it can be found as follows:

d = an + 1 – an

where

d is the difference of the arithmetic progression;

an + 1 – n + 1 member of the progression;

an is the n-th member of the progression.

From the problem statement, we know that the arithmetic progression is given by the following formula:

an = -3 * n – 3

Based on this, we can find its first and second members:

n = 1 => a1 = -3 * 1 – 3 = -3 – 3 = -6;

n = 2 => a2 = -3 * 2 – 3 = -6 – 3 = -9.

Then:

d = an + 1 – an = a2 – a1 = -9 – (-6) = -9 + 6 = -3

One of the components of a person's success in our time is receiving modern high-quality education, mastering the knowledge, skills and abilities necessary for life in society. A person today needs to study almost all his life, mastering everything new and new, acquiring the necessary professional qualities.